RESEARCH ARTICLE: Students’ perception of the learning environment in private-sector pharmacy institutes of Pakistan - Bashir, Samra; Khan, Arif-ullah; Mahmood, Maryam; Abbas, Mateen; Akhtar, Samar; Waheed Khan, Abdul; Tahir Aqeel, Muhammad; Akhlaq, Muhammad; Ahmad, Hamaad (Pharmacy Education, 2020)
Introduction: A conducive learning environment is crucial to the effective delivery of curriculum and professional and social development of the students. This cross-sectional study was conducted to investigate students’ perception of the learning environment in private-sector pharmacy institutes of Pakistan. Methods: The overall learning environment and its various aspects were compared between different pharmacy institutes, year of study and gender. Questionnaires, based on the Dundee Ready Education Environment Measure (DREEM) and demographic information, were completed by 527 undergraduate pharmacy students enrolled at six private-sector pharmacy institutes in Pakistan. Participants were selected by convenience sampling and the scores were compared across grouping variables identified via demographic information. Results: The total DREEM score across the sample was 116.10±25.39 (mean ± S.D), indicating an overall positive perception of the learning environment among students of the private-sector pharmacy institutes. Similarly, the sub- scale scores also reflected students’ positive perception of various aspects of the educational environment including learning, teachers, institutional atmosphere, academic self-perception and social self-perception across the sample. Total DREEM score and sub-scale scores were consistent between male and female students and across all years of Pharm. D. programme included in this study. Scores of the individual institutes reflect the prevalence of an overall conducive learning environment in the private-sector pharmacy institutes under study. A comparison of the total DREEM score and sub-scale scores of the individual institutes also reflects that learning environment of a few institutes, as perceived by their respective students, is significantly better than the others. Conclusion: The positive perception held by the students of private-sector pharmacy institutes in Pakistan is suggestive of the existence of a conducive learning environment that is contributory towards students’ learning of professional and social abilities.